TU-DAMD employment for molecular characterization of Salvia judaica and Salvia palaestina species - Saleh, Basel (Acta Biologica Szegediensis, 2021)
Genetic diversity in perennial Salvia judaica Boiss (Judean sage) and Salvia palaestina Benth (Palestinian sage) species using touch-up directed amplification of minisatellite region DNA (TU-DAMD) has been performed in two separated sets; in the first set (set A) the initial annealing temperature was increased from 50 °C to 55 °C, whereas, in the second one (set B), it increased from 55 °C to 60 °C by 0.5 °C/cycle during the first 10 PCR amplification cycles. Fifteen DAMD primers have been tested for each set. Set (A) produced 89.39% polymorphism level (P%) with polymorphic information content (PIC) average of 0.33 and marker index (MI) average of 3.96. Whereas, in set (B) these values were recorded to be 94.02%, 0.34 and 3.98 for P%, PIC and MI, respectively. Data showed that the two mentioned sets successfully highlighted high polymorphism level between the two studied Salvia sp. This work studies genetic diversity of S. judaica and S. palaestina species using TU-DAMD test as a novel molecular marker.